Prevalence of ocular disorders in Liberia: a retrospective study using the eyeSmart electronic medical record system - Anthony Vipin Das; Priyanka Kammari; Edward Bea Guizie; Rajashekar Varada; Gurcharan Singh (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background This study aims to describe the demographic distribution and ocular diagnosis of the patients presenting to the Liberia Eye Center, Monrovia, using the eyeSmart Electronic Medical Record system. # Methods A retrospective study was conducted on patients presenting to Liberia Eye Center from July 2017 to July 2018. A total of 5258 patients were examined during this period. Data was collected from eyeSmart Electronic Medical Record system database. The variables in the collected data include age, gender, location, occupation, socioeconomic status, laterality of eye affected, and ocular diagnosis. All the counties were included in the study. A total of 8234 instances of ocular diagnosis were made in 5258 patients. # Results Of the total 5258 patients, the majority of them presented from the county of Lofa (18.77%) and the least number of patients from Gbarpolu (1.62%). Out of the total children examined (16 years and under), females outnumbered males (8.25% vs. 4.87%). Among the adults, almost equal number of males (50.1%) and females (49.9%) presented to the clinic. The most common diagnosis was uncorrected refractive errors (34.89%) followed by the cornea and anterior segment disorders, cataract and glaucoma in that order. But in children aged 16 years and under, cornea and anterior segment related disorders (6.01%) were the most common diagnosis and the least common diagnosis was amblyopia (0.34%). Majority of the patients were unemployed (60.54%) and the most common profession in the remaining cohort was a student (8.96%). # Conclusions Refractive error was found to be the most common ocular diagnosis and the second most common presentation was cornea and anterior segment disorders in Liberian population. In children aged 16 years and under, cornea and anterior segment related disorders were the most common ocular diagnosis. The description of various ocular diseases and their clinical presentation for the first time in a Liberian population provides the opportunity for further research. The digitization of eye care using electronic medical record systems is a progressive step forward to help formulate strategies for health policy to combat avoidable blindness across Liberia.